Do ADHD Children With and Without Child Behavior Checklist–Dysregulation Profile Have Different Clinical Characteristics, Cognitive Features, and Treatment Outcomes?. (January 2015) - Peyre, Hugo; Speranza, Mario; Cortese, Samuele; Wohl, Mathias; Purper-Ouakil, Diane
Objective: The Child Behavior Checklist–Dysregulation Profile (CBCL-DP), characterized by elevated scores on the "Attention Problems, " "Aggressive Behavior, " and "Anxious/Depressed" scales in the CBCL, has been associated with later severe psychopathology. In a sample of children with ADHD, this study sought to further explore the clinical characteristics, the response to methylphenidate medication, and the cognitive features of ADHD children with CBCL-DP.Method: The sample consisted of 173 ADHD outpatients (age = 10.9 ± 2.81) assessed using symptom severity scales, personality questionnaires (Emotionality Activity Sociability [EAS] and Junior Temperament and Character Inventory [JTCI]), and neuropsychological tests. A subsample of 136 participants was reassessed after optimal adjustment of methylphenidate dosage. Results and Conclusion: Variables that were independently associated with CBCL-DP were clinical severity (ADHD Rating Scale [ADHD-RS]), internalized disorders, high emotionality (EAS), and low self-directedness (JTCI). CBCL-DP was associated neither with poorer response to methylphenidate nor with more side effects. There were no differences in cognitive performances between participants with and without CBCL-DP.